Effects of ocean acidification on the socio-ecological system of mitiliculture in southern Chile: Market impacts and challenges for future sustainability under hypothetical models - San Martín Montoya, Valeska Andrea
The effects of global change are modifying the fundamental characteristics of the oceans, generating variations in different physical-chemical parameters (e.g. temperature, salinity, oxygen, pH, among others). Greenhouse gas models indicate that an evident increase in the levels of atmospheric carbon dioxide (CO2) and, consequently, in the partial pressure of CO2, is leading to a decrease in pH in seawater, a process known as Acidification of the Ocean (AO). The AO is presented as one of the most important threats to the group of marine populations and ecosystems. Fishing and aquaculture are considered activities of economic and social importance, as well as being sources of protein, energy and essential nutrients, representing food security for a future human population in constant growth. In this context, several studies have focused on determining the effect on biological responses under the new conditions of global change in the oceans, but most of these studies have not considered the direct relationship that exists between species of commercial importance and the possible impact on the market, and may even have important repercussions for producers and consumers. This proposal intends to establish a transdisciplinary effort to reduce these gaps in the understanding of environmental effects in species of commercial importance, which could affect the economy and human well-being. The objective of this thesis is to evaluate the effect of exposure to a future AO scenario in the early and late development of the commercial species Mytilus chilensis, determining its sensitivity and possible variations in physical attributes (shell color and hardness) and nutritional (Omega3 fatty acids EPA and DHA, Vitamin B12 and proteins), which are defined as market indexes with possible effects on supply and demand. Along with the above, this study will contribute with the exploration and projection of the adaptive potential present in the mussel farming companies to face the consequences of global change. The methodological approach of these theses, considers a system of manipulation of the levels of pH/pCO2 in the laboratory through a mesocosm system, using seawater injected with CO2 to simulate CO2 and pH scenarios, both for current and future levels corresponding to the locality of Chiloé (pH 7,9 = control and pH 7,6 = low pH system). The organisms were obtained from a culture center located in Vilupulli, Isla grande de Chiloé (42°49'S and 73°78'W). The physical and nutritional responses of the bivalves were analyzed in a period of 30 and 120 days. Together, the elective preferences of consumers before different attributes of M. chilensis were analyzed with the purpose of predicting impacts in the market through demand. At the same time, we worked directly with the main players of the mussel farming in southern Chile, conducting surveys and interviews in order to explore the adaptive potential to innovate in management systems. The results showed negative effects in the physical and nutritional attributes associated with the exposure of bivalves to low pH conditions. Observing visual deterioration in the shells, presenting an erosion and whitish color, at the same time significantly decreased the concentrations of fatty acids, proteins and vitamin B12 in organisms exposed to low pH conditions. The evaluation of consumer preferences reflected that the main attributes considered when choosing a product to make their purchase were the appearance and then the nutritional level, these being precisely the attributes that were affected by the exposure to the OA. Regarding the analysis of the capacity that the industries have to anticipate and respond to these changes, the determining factors in the willingness to invest in the creation of the capacity to anticipate the changes were evaluated, the caules showed that the industry adapts in a heterogeneous and that financial assets and social capital impel the will to invest in the capacity of adaptation. The effects of global change on ecosystems and species are inevitable, which is why it is urgent to have adaptation strategies to avoid impacts and reduce the risk of economic progress and food security. This research contemplates the orientation towards groups related to the mussel farming in order to provide knowledge to reduce or anticipate the impact of climate change with the development of strategies, providing support tools to stakeholders and learning about complex dynamics existing in systems socio-ecological. Los efectos del cambio global están modificando las características fundamentales de los océanos, generando variaciones en diferentes parámetros físico-químicos (e.g. temperatura, salinidad, oxígeno, pH, entre otros). Los modelos de gases de efecto invernadero indican que un evidente incremento en los niveles de dióxido de carbono (CO2) atmosférico y en consecuencia en la presión parcial de CO2, esta llevando a un descenso del pH en el agua de mar, proceso conocido como Acidificación del Océano (AO). La AO se presenta como una de las amenazas más importantes para el conjunto de poblaciones marinas y ecosistemas. La pesca y acuicultura son consideradas actividades de importancia económica y social, además de ser fuentes de proteína, energía y nutrientes esenciales, representando la seguridad alimentaria para una futura población humana en constante crecimiento. En este contexto variados estudios se han centrado en determinar el efecto en respuestas biológicas bajo las nuevas condiciones de cambio global en los océanos, pero la mayoría de estos estudios no han considerado la relación directa que existe entre especies de importancia comercial y el posible impacto en su mercado, pudiendo llegar a tener repercusiones importantes para productores y consumidores. En esta propuesta se pretende establecer un esfuerzo transdisciplinario para reducir estos vacíos en la comprensión de los efectos ambientales en especies de importancia comercial, los cuales podrían llegar a afectar la economía y el bienestar humano. La presente tesis doctoral tiene como objetivo evaluar el efecto de la exposición a un futuro escenario de AO en el desarrollo temprano y tardío de la especie comercial Mytilus chilensis, determinando su sensibilidad y posibles variaciones en atributos físicos (color y dureza de concha) y nutricionales (ácidos grasos Omega3 EPA y DHA, Vitamina B12 y proteínas), los cuales son definidos como índices de mercado con posibles efectos en la oferta y demanda. Junto con lo anterior, este estudio aportará con la exploración y proyección del potencial adaptativo presente en las empresas de mitilicultura para enfrentar las consecuencias del cambio global. El enfoque metodológico de estas tesis, considera un sistema de manipulación de los niveles de pH/pCO2 en el laboratorio mediante un sistema de mesocosmo, utilizando agua de mar inyectada con CO2 para simular escenarios de CO2 y pH, tanto para niveles actuales y futuros, correspondientes a la localidad de Chiloé (pH 7,9=control y pH 7,6=sistema bajo de pH). Los organismos fueron obtenidos desde un centro de cultivo ubicado en la localidad de Vilupulli, Isla grande de Chiloé (42°49´S y 73°78´O). Se analizaron las respuestas físicas y nutricionales de los mitílidos en un periodo de 30 y 120 días. Conjuntamente se analizaron las preferencias electivas de los consumidores antes diferentes atributos de M. chilensis con la finalidad de predecir impactos en el mercado a través de la demanda. A la vez, se trabajó directamente con los principales actores de la actividad mitilicultora del sur de Chile, realizando encuestas y entrevistas con la finalidad de explorar el potencial adaptativo de la mitilicultura para innovar en sistemas de gestión. Los resultados mostraron efectos negativos en los atributos físicos y nutricionales asociados a la exposición de los mitílidos a condiciones de bajo pH. Observando deterioro visual en las conchas, presentando una erosión y color blanquecino, a la vez disminuyeron significativamente las concentraciones de ácidos grasos, proteínas y vitamina B12 en los organismos expuestos a condiciones de bajo pH. La evaluación de preferencias del consumidor reflejaron que los principales atributos considerados al momento de elegir un producto para efectuar su compra fueron la apariencia y luego el nivel nutricional, siendo estos justamente los atributos que fueron afectados por la exposición a la AO. En cuanto al análisis de la capacidad que tienen las industrias para anticipar y responder a estos cambios, se evaluaron los factores determinantes en la disposición a invertir en la creación de la capacidad para anticipar los cambios, los cuales mostraron que la industria se adapta de manera heterogénea y que los activos financieros y el capital social impulsan la voluntad de invertir en la capacidad de adaptación. Los efectos del cambio global en ecosistemas y especies son inevitables, es por ello que es urgente contar con estrategias de adaptación para evitar impactos y disminuir el riesgo del progreso económico y la seguridad alimentaria. Esta investigación contempla la orientación hacia grupos relacionados con la empresa mitilicultora con el fin de entregar conocimiento para disminuir o anticipar el impacto del cambio global con el desarrollo de estrategias,proporcionando herramientas de apoyo a las partes interesadas y el aprendizaje sobre dinámicas complejas existentes en sistemas socio-ecológicos.